Design and Analysis of 5G Telemedicine Systems - Chettri, Lalit; Bera, Rabindranath (Mobile and Forensics, 2021)
Recently, remote health care is one of the serious issues to look after. Due to lack of technological advancement, the services in heath have been degrading. This work details about design of 5G Wireless communication systems and further it is implemented in telemedicine systems. As 5G deals with FBMC as a selected waveform and this has been chosen because it has the higher spectrum allocation capability and better interference rejection as compared to that of other multicarrier techniques. The main motivation to jump into 5G technologies is because of more connected devices and it can allocate the underutilized spectrum to the secondary user verifying the certain policies. As these telemedicine systems is one of the most needed technologies in health care especially in remote places and 5G systems has higher data rate where the health specialist can receive the patient status at less time and act as per the condition. This work details about transmission of patient’s vital sign, image and video and analysis which are most essential components in future Telemedicine systems.